1997
DOI: 10.1542/peds.99.1.44
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Transluminal Angioplasty for Renovascular Hypertension in Children: Initial and Long-term Results

Abstract: Aortoarteritis is the most common cause of renovascular hypertension in South Asian children. PTRA is safe and highly effective and therefore should be the treatment of choice in pediatric renovascular hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
87
3
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(97 citation statements)
references
References 24 publications
4
87
3
3
Order By: Relevance
“…This can be achieved through percutaneous angioplasty and surgical interventions. In severe cases, where none of the previous treatments is successful, a nephrectomy is an alternative [1][2][3][4][5][6][7][8][9].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This can be achieved through percutaneous angioplasty and surgical interventions. In severe cases, where none of the previous treatments is successful, a nephrectomy is an alternative [1][2][3][4][5][6][7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…Percutaneous transluminal renal angioplasty has been considered the treatment of choice for revascularization [1,[4][5][6]. In cases, angioplasty had been reported as very useful, but other authors have reported poor long-term results needing the use of stents [1,[10][11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The long-term success rate seems, at present, to be between 50 and 90% with technical failures or late stenosing events being the most important problems [3,[10][11][12]. The technical failures are with increasing experience and improving equipment getting less common.…”
Section: Angioplasty With or Without Stentingmentioning
confidence: 99%